Crossing Boundaries: Khumalo the tightrope walker. Issue 1 (2nd January 2023) - Badal, Bernice
ABSTRACT: The curriculum does not exist in a vacuum: its construction, mediation and enactment are subject to a range and pitch of voices which are not always in concert. This article addresses an enduring concern about the influence of teacher's voice in educational change contexts, given that scholarship identifies a diminishing space for teacher voice(s). It presents teacher voice, catalysed by teacher agency that explicates the impact of inner conversations on teachers' capacity to negotiate both internal and external constraints and manifest a stance that accommodates the employer and the self. Theoretical concepts are drawn from Bandura's Social cognitive theory incorporating the triadic causation model of agency. This qualitative case study, therefore, examined the political, contextual and personal determinants of teacher agency through analysis of the data derived from a broader study. The efforts of one teacher from a township school are highlighted to show how his perceptions, characteristics, and mediations of a 'teacher proof' reform lead to the construction of a unique proactively compliant teacher voice which adds to the stances in the findings of curriculum studies. This article has as its focus teachers' capacity to cross metaphorical boundaries and establish a crucial role in the construction and dissemination of knowledge in a situated context in South Africa.